Porosity and free gas estimates from controlled source electromagnetic data at the Scanner Pockmark in the North Sea. (July 2021) - Gehrmann, Romina A.S.; Provenzano, Giuseppe; Böttner, Christoph; Marín-Moreno, Héctor; Bayrakci, Gaye; Tan, Yee Y.; Yilo, Naima K.; Djanni, Axel T.; Weitemeyer, Karen A.; Minshull, Timothy A.; Bull, Jonathan M.; Karstens, Jens; et al.
Highlights: Multidisciplinary approach to estimate physical properties using controlled source electromagnetic, seismic reflection and core logging data. In the Scanner Pockmark area in the Central North Sea glaciomarine sediment porosity decreases in the top 150 mbsf from 50 ± 10 % to 25 ± 3 % due to compaction. Gas concentrations estimated from resistivity models are up to 34 ± 14 % in a glacial till deposit that forms an intermediate reservoir in an active fluid migration and venting system. Abstract: We present porosity and free gas estimates and their uncertainties at an active methane venting site in the UK sector of the North Sea. We performed a multi-disciplinary experiment at the Scanner Pockmark area in about 150 m water depth to investigate the physical properties of fluid flow structures within unconsolidated glaciomarine sediments. Here, we focus on the towed controlled source electromagnetic (CSEM) data analysis with constraints from seismic reflection and core logging data. Inferred background resistivity values vary between 0.6–1 Ω m at the surface and 1.9–2.4 Ω m at 150 mbsf. We calibrate Archie's parameters with measurements on cores, and estimate porosities of about 50 ± 10 % at the seafloor decreasing to 25 ± 3 % at 150 mbsf which matches variations expected for mechanical compaction of clay rich sediments. High reflectivity in seismic reflection data is consistent with the existence of a gas pocket. A synthetic study of varying gas content in this gas pocket shows that at least 33 ± 8 % of free gas is required to cause a distinct CSEM data anomaly. Real data inversions with seismic constraints support the presence of up to 34 ± 14 % free gas in a 30–40 m thick gas pocket underneath the pockmark within the stratigraphic highs of a till layer above the glacial unconformity in the Aberdeen Ground Formation.